2014
DOI: 10.1073/pnas.1404321111
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic signals of summer denitrification in a northern hardwood forested catchment

Abstract: Despite decades of measurements, the nitrogen balance of temperate forest catchments remains poorly understood. Atmospheric nitrogen deposition often greatly exceeds streamwater nitrogen losses; the fate of the remaining nitrogen is highly uncertain. Gaseous losses of nitrogen to denitrification are especially poorly documented and are often ignored. Here, we provide isotopic evidence (δ 15 N NO3 and δ 18 O NO3 ) from shallow groundwater at the Hubbard Brook Experimental Forest indicating extensive denitrifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 49 publications
3
67
0
Order By: Relevance
“…4d), revealing the same pollution sources for these two pollutants. C:N ratio was a good indicator for resources that can be used by microbes, such as denitrification bacteria (Fang et al, 2015;Wexler et al, 2014). C:N ratio was sharply reduced with increase of NH þ 4 concentration, for which exceeding 10.0 mg N L À1 reduced the C:N ratio to round 5, although further increase of NH þ 4 concentration did not continue reduce the C:N ratio.…”
Section: Resultsmentioning
confidence: 99%
“…4d), revealing the same pollution sources for these two pollutants. C:N ratio was a good indicator for resources that can be used by microbes, such as denitrification bacteria (Fang et al, 2015;Wexler et al, 2014). C:N ratio was sharply reduced with increase of NH þ 4 concentration, for which exceeding 10.0 mg N L À1 reduced the C:N ratio to round 5, although further increase of NH þ 4 concentration did not continue reduce the C:N ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The same case also occurs in the northern hardwood forests at the Hubbard Brook Experimental Forest in the White Mountains of New Hampshire, USA. Wexler et al (2014) found that both δ 15 N-NO 3 − and δ 18 O-NO 3 − values of a few samples fell below the denitrification line, which might be attributed to a mix of partially denitrified NO 3 − in groundwater and the NO 3 − in stream water when a hyporheic flow path brought water from the stream to the shallow groundwater in the riparian zone. One possible means of differentiating denitrification from the mixing of source materials is to analyze the relationship between δ 15 N-NO 3 − values (or δ 18 O-NO − 3 ) and NO 3 − concentrations ).…”
Section: Stable Isotope Approach For Identifying Nitrogen Transformatmentioning
confidence: 92%
“…Denitrification causes both δ 15 N and δ 18 O values of the residual NO 3 − to increase. Sigman et al (2005) and Granger et al (2008)) found that δ 15 N and δ 18 O values of residual NO 3 − increased at a ratio of 2 during denitrification.However, some other surface and groundwater studies found that denitrification caused δ 18 O and δ 15 N to increase at a ratio of more than 1:1(Minet et al 2012; Dale et al 2014a, b) and some closed to 2(Burns et al 2009;Baily et al 2011;Critchley et al 2014;Wexler et al 2014) in agricultural watersheds. However, these lower ratios were not found in urban watersheds(Kaushal et al 2011), presumable because denitrification was limited by less organic carbon(Barnes and Raymond 2010;Wong et al 2015).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Whitfield et al (2010) more significant in wet soils than dry soils. In areas where soil acidification is a concern, denitrification can be an important mitigating process as it prevents excess NO 3 -from entering groundwater (Wexler et al 2014). However, in many such areas (e.g., well-drained, sandy upland forest soils), denitrification is often negligible, if not absent.…”
Section: Explanation and Comparison Of Data Inputs Used In The Simplementioning
confidence: 99%